2013
DOI: 10.5214/ans.0972.7531.200304
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic evaluation of blink reflex as a tool for early diagnosis of neurological dysfunction in patients of hypothyroidism.

Abstract: BackgroundNeurological dysfunction is an important consequence of hypothyroidism. Some of the neurologic manifestations of hypothyroidism include somnolence, lethargy, impaired memory and concentration, depression and entrapment neuropathy. Rarer but reversible neurological manifestations include cerebellar ataxia, psychosis, dementia and myxedema coma.PurposeThe aim of the present study was to evaluate the usefulness of the blink reflex as a method for obtaining an early diagnosis of central nervous system dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Multiple cranial neuropathy is an uncommon clinical finding in hypothyroidism, which is an important differential diagnosis in the workup of new neurological deficits [11]. Another study reported that electrophysiological evaluation, such as blink reflex responses in hypothyroid patients, may be useful in screening for neurological dysfunction in patients [12]. Although there is still insufficient evidence of a definitive relationship between neurological disorders and thyroid diseases, many studies have found an association between them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple cranial neuropathy is an uncommon clinical finding in hypothyroidism, which is an important differential diagnosis in the workup of new neurological deficits [11]. Another study reported that electrophysiological evaluation, such as blink reflex responses in hypothyroid patients, may be useful in screening for neurological dysfunction in patients [12]. Although there is still insufficient evidence of a definitive relationship between neurological disorders and thyroid diseases, many studies have found an association between them.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that thyroid hypofunction may worsen physical and emotional problems in HFS patients. The reason why thyroid hypofunction worsens surgical outcomes in HFS, which is considered a hyperfunctional condition of the nervous system, may be because insufficient thyroid hormones affect the central and peripheral nervous systems through their role in gene expression, myelin production, neurotransmitter system, or axonal transportation and are associated with emotional function [12, 20, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Myelination is the most important factor determining conduction velocity 12 . Metabolic alteration caused by hormonal imbalance affects Schwann cells, inducing a segmental demyelination 14 . Demyelination can also occur as a result of oxidative damage to myelin sheath 15 .…”
Section: Discussionmentioning
confidence: 99%